Analysis of Fraud in Civil on Agreements Resulting in Default - Catur Erwin Setiawan; Suwarti Suwarti; Nam Rumkel (Syntax Corporation Indonesia, 2021)
This study aims to analyze in-depth the fraud based on Article 1328 of the Civil Code on the agreement that can result in default, as well as to examine the legal consequences of the agreement containing elements of fraud based on Article 1328 of the Civil Code, fraud can be canceled or null and void. The research method used in this research is normative research on the rule of law contained in Article 1328 of the Civil Code. The data used in this study is secondary data. The secondary data used in this study consists of primary legal materials that are authoritative which means they have authority, secondary legal materials, and tertiary legal materials. The results of this study indicate that fraud based on Article 1328 of the Civil Code in the Agreement does not result in Default. Because default and fraud in civil law have different elements. Default is regulated in Article 1243 of the Civil Code, while fraud in civil law is regulated in 1328 of the Civil Code. The consequences of an agreement containing an element of fraud can be canceled or null and void by law. The condition for canceling the agreement is that the agreement to be canceled must be reciprocal, namely an agreement that gives rights and obligations to both parties, cancellation is carried out through the court so that the cancellation of the agreement is through a judge's decision, and there must be a default. An agreement can be canceled as stipulated in article 1321 of the Civil Code, while an agreement that has prohibited things causes the agreement to be null and void, based on Article 1254 of the Civil Code.